Pembuatan Alat Potong Tulang Sapi untuk Peningkatan Kinerja Panitia Qurban di Masjid Miftahul Jannah Kelurahaan Berua Kota Makassar - Alang Sunding; Nurul Afifah (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Every 10th of Dhul-Hijjah Muslims around the world celebrate eid al-Adha or known as the feast of Qurban. Almost every mosque, especially urban areas, organizes slaughter of qurban animals, as well as in the Miftahul Jannah Mosque. Based on information obtained from partners that almost every year the number of cows is more than goats for slaughter. In addition to meat, beef bones are also a part that is distributed by partners to those who are entitled to receive especially the shohibul qurban. In the resent years the bones that are distributed are large pieces so that it is a concern for partners because the recipient expects the size of the bone received to be ready to be cooked because not all residents who have equipment to cut bones. Based on this condition, it is necessary to make a bone cutting machine that can cut bones quickly with a ready-to-cook size of 10-15 cm. Utilization of bone cutting tools was carried out on eid al-Adha 10 Dhul-Hijjah 1442 H, coinciding on July 20, 2021. The number of cows that are cut is 6.  The results of the implementation of the machine show that the equipment is functioning in accordance with the expectations of the partner. Based on the results of four  mitra members showed that the machine can be operated easily, can cut quickly with a cut size of 10 - 15 cm, and is safe to use. After cutting 6 cow bones the machine still works well. Some input from partners is to expand the size of the table and improve the appearance of the machine so that it can be sold.